Frequency domain analysis-based optimal configurations and energy dissipation performance of combined damped outrigger systems. (June 2021) - Zhou, Ying; Lu, Decheng; Xing, Lili; Aguaguiña, Mario
Abstract: This paper investigates optimal configurations of combined damped outrigger systems (CDOs) using the newly proposed frequency domain analysis-based simplified models. The CDOs are constructed by the viscous-damper outrigger and the buckling-restrained-brace outrigger arranged vertically in different heights. This paper includes two types, CDO_11 (buckling-restrained-brace outrigger above viscous-damper outrigger), and CDO_22 (viscous-damper outrigger above buckling-restrained-brace outrigger). First, the paper proposes a simplified analytical model of a general outrigger system to derive a theoretical solution for the dynamic response of the structure in the time domain. Then, the solution in the time domain is transformed to the frequency domain via the Laplace transformation. The first-mode frequency response function is used to obtain the optimal locations for different types of outrigger systems. Finally, this paper compares the vibration characteristics of the outrigger systems in terms of the amplitude, phase, and variance of the response.